Nilai-Nilai Pendidikan Karakter Religius Dalam Buku Seni Merayu Tuhan Karya Husein Ja’far Al Hadar Dan Relevansinya Terhadap Pendidikan Islam Era Milenial - Al Khirzin, Fazaa Daffa; Rohmad, Rohmad (Jurnal Ilmiah Wahana Pendidikan, 2024)
In the millennial era, there are many moral cases that are rife around us, both through social media and directly in the surrounding environment. This phenomenon is the background of this research. To deal with this, the importance of character education becomes urgent. Character education is an effort to develop and shape the psychological aspects, morals, and character of a person to become better. The purpose of writing this thesis is to describe and analyze the values of religious character education in the book The Art of Seducing God and their relevance to the development of Islamic education in the current millennial era. This research includes library research. The data sources used in this study consisted of primary data sources, namely the book The Art of Seducing God, secondary data consisting of books, journals and other documents that support data acquisition and are related to the research title. The data collection technique used was a documentation technique with a content analysis technique using the Krippendorf model, used by researchers to describe the content of religious character education values in the book The Art of Seducing God by Husein Ja'far Al Hadar. The results of the research that has been carried out refer to Jusuf Amir Feisal's opinion through his book Reorientation of Islamic Education which is analyzed and then applied to take the values of religious character education which shows that there are three main values, namely faith, morality and sharia (worship). By applying the values of Islamic religious character education in the aspects of faith, morals, and sharia (worship), the development of Islamic education in the millennial era can provide a strong foundation for the millennial generation to face the challenges of modern times. Through correct understanding, good morals, and proper practice of worship, it is hoped that the millennial generation will become individuals who care about religion, are able to face technological developments wisely, and practice their religious teachings well in everyday life. And being able to make the best use of technology to improve faith and spiritual life, without being swayed by the negative impact of an all-sophisticated era.